Infection with an asymptomatic virus in rice results in a delayed drought response - Encabo, Jaymee R.; Macalalad-Cabral, Reena Jesusa A.; Matres, Jerlie Mhay K.; Coronejo, Sapphire Charlene Thea P.; Jonson, Gilda B.; Kishima, Yuji; Henry, Amelia; Choi, Il-Ryong (Commonwealth Scientific and Industrial Research Organisation, 2020)
Infection of viruses in plants often modifies plant responses to biotic and abiotic stresses. In the present study we examined the effects of Rice tungro spherical virus (RTSV) infection on drought response in rice. RTSV infection delayed the onset of leaf rolling by 1–2 days. During the delay in drought response, plants infected with RTSV showed higher stomatal conductance and less negative leaf water potential under drought than those of uninfected plants, indicating that RTSV-infected leaves were more hydrated. Other growth and physiological traits of plants under drought were not altered by infection with RTSV. An expression analysis of genes for drought response-related transcription factors showed that the expression of OsNAC6 and OsDREB2a was less activated by drought in RTSV-infected plants than in uninfected plants, further suggesting improved water status of the plants due to RTSV infection. RTSV accumulated more in plants under drought than in well-watered plants, indicating the increased susceptibility of rice plants to RTSV infection by drought. Collectively, these results indicated that infection with RTSV can transiently mitigate the influence of drought stress on rice plants by increasing leaf hydration, while drought increased the susceptibility of rice plants to RTSV.